Disaster Education for Young Children: A Systematic Review and Thematic Analysis - Feyza Tantekin Erden; Elif Güvelioğlu (Sakarya University Journal of Education)
The aim of this systematic review is to search for, gather, and synthesize studies on disaster education for children in the early childhood period. Studies that implemented and evaluated the results of a disaster education program for children aged 3 to 6 years old were examined. For the purpose of this study, the focus was on disasters caused by nature induced hazards (earthquake, wildfire, tsunami, flood, volcano eruption, storm, avalanche, tornado, landslide, hurricane, blizzard). A large number of diverse databases such as Emerald, ERIC, JSTOR, ProQuest, SAGE Journals Online, Science Direct, Scopus, SpringerLink, Taylor & Francis Online Journals, Web of Science, Wiley Online Library were searched using a wide range of keywords, resulting in the identification of seven studies from peer-reviewed journals. These studies were examined through thematic analysis. The results highlight the different strategies and materials that researchers utilized for teaching young children about disasters, as well as the various evaluation methods used to assess young children's disaster-related knowledge. Furthermore, it was found that across all examined studies, there was a positive impact of disaster education on children’s disaster related knowledge. It is hoped that this review will shed light on an underrated yet crucial research area, attracting more attention and providing a starting point for rapid improvement